Análisis comparativo de metodologías en arquitectura de la información aplicadas a contextos empresariales (2016)
Everyday diverse companies in the word, regardless of their size, economic activity, or capital managed, invest large sums of money in technology to meet the specific needs of a certain area determined by the company. This causes data disintegration, redundancy, as well as generating operation, integration, and standardization costs. Additionally, companies cannot count on daily updated and consolidated information. Because of this, it has become increasingly relevant to have a method based on an integral view of the company. This method would allow the alignment of processes, data application, and technological infrastructure with the strategic objectives or purpose of the company in mind. In this way, the correct alignment of technology and business processes can be guaranteed with the purpose of reaching the company’s strategic goals. All of this can be achieved if the company counts on Business Information Architecture which satisfies these requirements. Therefore, this article presents a comparison between different information architecture models and the criteria necessary to develop and implement these methods within an organization.